2021
DOI: 10.1021/acssensors.1c01022
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensor Detection of Synthetic Auxins In Planta using Corona Phase Molecular Recognition

Abstract: Synthetic auxins such as 1-naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) have been extensively used in plant tissue cultures and as herbicides because they are chemically more stable and potent than most endogenous auxins. A tool for rapid in planta detection of these compounds will enhance our knowledge about hormone distribution and signaling and facilitate more efficient usage of synthetic auxins in agriculture. In this work, we show the development of real-time and nondestructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 63 publications
0
28
0
1
Order By: Relevance
“… (A) Paper-based electro-analytical device used in detection of H 2 O 2 in circular plant samples punched out of the tomato leaves (Sun et al, 2020 ); (B) Miniaturized electrochemical sensor inserted into tomato fruits for detection of auxin precursor, Tryp (Yang et al, 2021 ); (C) in situ ABA electrochemical sensor assembled onto a microneedle array for detection in fruits (Wang et al, 2021 ); (D) Current-time curves generated when the ABA microneedle sensor is inserted into cucumber where ABA concentrations is linearly correlated with the step current observed (Wang et al, 2021 ); (E) in situ SA electrochemical sensor arranged in an IDME array for insertion into cucumber leaves (Liu et al, 2021 ); (F) Response current (top) and derived SA concentration (bottom) obtained from the IDME array sensor in 5 different live cucumber leaves (Liu et al, 2021 ); (G) Brightfield (left) and corresponding false-colored images (right) of a spinach leaf infiltrated with H 2 O 2 (red arrow) and reference (blue arrow) nanosensors on both sides of the leaf mid-vein. False-colored images shows the transient H 2 O 2 wave upon mechanical wounding of the leaf at t = 0 min (Lew et al, 2020b ); (H) H 2 O 2 nanosensor response to different types of stress applied to the plant, including mechanical wounding (red), flg22 treatment (green), high light (orange) and high heat (blue) stresses (Lew et al, 2020b ); (I) Real-time sensing of 2,4-D uptake in hydroponically grown pak choi and rice leaves using nanosensors which illustrated a turn-on response observed in pak choi but not in rice over a time-period of 5 h (Ang et al, 2021 ); (J) Arsenite nanobionic sensor infiltrated into hyperaccumulator plant Pteris creticas fern, showing intensity changes corresponding to arsenic accumulation detected over 7-day time period upon arsenite exposure (Lew et al, 2021 ); (K) Schematic of standoff detection of nitroaromatic compound, picric acid, using nanosensors with real-time information relayed from the nanosensor-infiltrated plant to a portable Raspberry Pi-based electronic device (Wong et al, 2017 ). …”
Section: Electrochemical Sensors For In Planta Mon...mentioning
confidence: 99%
See 1 more Smart Citation
“… (A) Paper-based electro-analytical device used in detection of H 2 O 2 in circular plant samples punched out of the tomato leaves (Sun et al, 2020 ); (B) Miniaturized electrochemical sensor inserted into tomato fruits for detection of auxin precursor, Tryp (Yang et al, 2021 ); (C) in situ ABA electrochemical sensor assembled onto a microneedle array for detection in fruits (Wang et al, 2021 ); (D) Current-time curves generated when the ABA microneedle sensor is inserted into cucumber where ABA concentrations is linearly correlated with the step current observed (Wang et al, 2021 ); (E) in situ SA electrochemical sensor arranged in an IDME array for insertion into cucumber leaves (Liu et al, 2021 ); (F) Response current (top) and derived SA concentration (bottom) obtained from the IDME array sensor in 5 different live cucumber leaves (Liu et al, 2021 ); (G) Brightfield (left) and corresponding false-colored images (right) of a spinach leaf infiltrated with H 2 O 2 (red arrow) and reference (blue arrow) nanosensors on both sides of the leaf mid-vein. False-colored images shows the transient H 2 O 2 wave upon mechanical wounding of the leaf at t = 0 min (Lew et al, 2020b ); (H) H 2 O 2 nanosensor response to different types of stress applied to the plant, including mechanical wounding (red), flg22 treatment (green), high light (orange) and high heat (blue) stresses (Lew et al, 2020b ); (I) Real-time sensing of 2,4-D uptake in hydroponically grown pak choi and rice leaves using nanosensors which illustrated a turn-on response observed in pak choi but not in rice over a time-period of 5 h (Ang et al, 2021 ); (J) Arsenite nanobionic sensor infiltrated into hyperaccumulator plant Pteris creticas fern, showing intensity changes corresponding to arsenic accumulation detected over 7-day time period upon arsenite exposure (Lew et al, 2021 ); (K) Schematic of standoff detection of nitroaromatic compound, picric acid, using nanosensors with real-time information relayed from the nanosensor-infiltrated plant to a portable Raspberry Pi-based electronic device (Wong et al, 2017 ). …”
Section: Electrochemical Sensors For In Planta Mon...mentioning
confidence: 99%
“…It complements popular agricultural techniques used by farmers to maximize yield including crop rotation, intercropping and genetic modification (Uzogara, 2000 ; Wang et al, 2014 ; Yang et al, 2020 ). It also allows the precise calibration of optimal dosage and application of agrichemicals such as pesticides, herbicides or plant growth regulators (Ang et al, 2021 ; Roper et al, 2021 ). However, current chromatography-based analytical techniques are limiting the potential of plant health monitoring in influencing farm management decisions on a day-to-day basis (Pan et al, 2010 ; Balcke et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being highly hydrophobic nanostructures, SWCNTs can be easily suspended in aqueous solution using noncovalent functionalization by polymers, DNA, RNA, dendrons, proteins, peptides, or specific recognition elements like antibodies or aptamers [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ]. Only functionalized, suspended SWCNTs reveal a fluorescence signal.…”
Section: Introductionmentioning
confidence: 99%
“…Only functionalized, suspended SWCNTs reveal a fluorescence signal. Several studies demonstrated the feasibility of SWCNTs as fluorescence sensors or markers in vivo [ [46] , [47] , [48] , 51 , 59 , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ]. For example, single nanoparticle tracking of SWCNTs in the extracellular space of live brains could locally resolve its dimensions and viscosity [ 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Diese Te chnik wurde angewendet, unter anderem zur Detektion von genetischem Material, [20] Proteinen, [21,22] Lipiden, [23] bakteriellen Motiven [24] oder kleinen Signalmolekülen wie Neurotransmitter, [19,25] reaktiven Sauerstoffspezies (ROS) [26][27][28] oder Stickstoffmonoxid (NO). [29] In jüngerer Zeit ermçglichte ihre Verwendung als nicht genetisch kodierte Sensoren die Visualisierung von ROS-Mustern, [27,30,31] Auxinen [32] oder der Schwermetallaufnahme [33] in Pflanzen. [34] Um die SWCNT-Sensoreigenschaften maßzuschneidern, wurden verschiedene chemische Designstrategien fürd ie Oberflächenfunktionalisierung entwickelt.…”
Section: Introductionunclassified